Hubungan Self-Esteem dengan Motivasi Belajar Remaja Panti Asuhan ‘Aisyiyah Daerah Cabang Lubuk Bagalung Padang - Hermivia Olva; Yulidar Ibrahim; Marjohan Marjohan (Jurnal Konseling dan Pendidikan, 2014)
The teenager who have more motivation in studying will do many activities that be useful in learning process. If they are able to think and make sure about their will have more motivation to study, have a good socialization and can manage their passion. The purpose of the research is analyzing about correlation between self-esteem with motivation in studying of  teenage orphanage ‘Aisyiyah Lubuk Bagalung Padang. Kind of research is quantitative by using correlation descriptive. The subjects of the research are 30 students. The instruments are inventory and questionnaires. The result of the research shows that there are correlation between self-esteem and motivation in studying significantly by lowing correlation.